Comparison of Treatment Outcome of Humeral Shaft Fractures Treated with Functional Cast Brace and "U" Slab - Amaar Talib; Ahmed, Naveed; Omer Fraz; M. Omer Aziz; Fahad Javid; Neha Waqas (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the outcome of humeral shaft fractures treated by functional cast brace versus "U" slab in terms of union. Study Design: Quasi-experimental study Place and Duration of Study: Department of Orthopaedic Surgery/Traumatology Unit-II, Mayo Hospital, Lahore, Pakistan from Jul to Dec 2018. Methodology: One hundred and four patients fulfilling inclusion criteria were included. Patients were randomised into two groups by random tables. Group-A patients were treated with a "U" slab outdoors, and Group-B patients were treated with a customised functional brace from the Orthopaedic workshop as indoor cases. Results: The mean age of patients was 47.99±14.15 years, with minimum and maximum ages of 16 and 65 years, respectively. According to the operational definition, the union was achieved in 88(84.6%) patients. In Group-A, 38(73.1%) patients and in Group-B, 50(96.2%) patients had union. A significant association between union and study Groups was noted, i.e. Group B had a high union rate when compared to Group A, with a p-value of 0.001. Conclusion: To conclude, in patients with humeral shaft fracture, a functional cast brace is a better choice for achieving union as it reduces the burden of non-union, and patients recover early, assessed by callous formation.